Use pattern analysis in green open spaces of Malaysia - Abdul Malek, Nurhayati (2013)
Housing development in Malaysia is bounded to obey several acts and legislation which among them is the Planning Guidelines and Standards set out by the Town and Country Planning Department of Malaysia. This guideline serves as a written statement that contains guides that become reference in advancing any development. It is used by local planning authorities in controlling activities in land development for uniform, comfortable and safe execution. Among the most important guidelines closest to the policy in providing recreational area to a community is the Guideline on Recreation and Open Spaces, under Act A933 (Garispanduan Tanah Lapang dan Rekreasi, Pindaan 1995, Akta (A933), Seksyen 2(f), Bil No. 21/97 and The Town and Country Act, 172 (Akta Perancangan Bandar dan Desa, 1976 (Akta 172.). The policy also calls for recreational areas to be gazette and for their development to be monitored, for environmentally sensitive areas to be protected and for green areas to be established as buffer zones to limit urban development. However, the specific guidelines in developing Neighbourhood Parks are hardly stated. Merely an indication of a general and very broad guideline which stipulates a 10% of open spaces and recreation must be provided in any residential development, commercial development as well as in industrial developments. This is what Malaysia is experiencing now. Housing development especially in Malaysia has now grown to a stage where location relative to the nearest park or green area contributes to the most highly regarded property. This research have concluded that in order to explore the current Malaysian policy on green open spaces an analysis of use pattern of the users who uses the green open spaces is needed. This research is important as it helps to verify how green open spaces could complement the existing planning guidelines into developing a more user specific needs in all outdoor recreational venues.